1990
DOI: 10.1007/bf01868636
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of maxi-K+ channels on pancreatic duct cells by cyclic AMP-dependent phosphorylation

Abstract: Using the patch-clamp technique we have identified a Ca2(+)-sensitive, voltage-dependent, maxi-K+ channel on the basolateral surface of rat pancreatic duct cells. The channel had a conductance of approximately 200 pS in excised patches bathed in symmetrical 150 mM K+, and was blocked by 1 mM Ba2+. Channel open-state probability (Po) on unstimulated cells was very low, but was markedly increased by exposing the cells to secretin, dibutyryl cyclic AMP, forskolin or isobutylmethylxanthine. Stimulation also shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 44 publications
0
58
0
1
Order By: Relevance
“…Such Ca2+-activated K+ channels sensitive to cAMP-dependent phosphorylation have been found in cultured kidney cells (Guggino, Suarez-Isla, Guggino & Sacktor, 1985) and in pancreatic duct cells (Gray, Greenwell, Garton & Argent, 1990).…”
Section: Two Types Of K+ Currents In the T84 Cell Linementioning
confidence: 98%
“…Such Ca2+-activated K+ channels sensitive to cAMP-dependent phosphorylation have been found in cultured kidney cells (Guggino, Suarez-Isla, Guggino & Sacktor, 1985) and in pancreatic duct cells (Gray, Greenwell, Garton & Argent, 1990).…”
Section: Two Types Of K+ Currents In the T84 Cell Linementioning
confidence: 98%
“…3a) [97,98]. The driving force for anion transport is kept by opened K + channels [91,[99][100][101][102]. Interestingly, in rat pancreatic ducts UTP (which activates rat P2Y 2 and P2Y 4 receptors with about equal efficiency) decreased the whole-cell K + conductance and no effect on the Cl − conductance could be detected [94].…”
Section: Pancreatic Acinimentioning
confidence: 99%
“…The molecular identity of the channels was subsequently determined as the MaxiK channels encoded by KCNMA1 (Nehrke et al 2003;Romanenko et al 2006) and the IK1 channels encoded by KCNN4 (Begenisich et al 2004;Hayashi et al 2004), respectively. In the pancreatic duct, MaxiK seems to be the major channel maintaining a negative membrane potential during stimulated bicarbonate secretion (Gray et al 1990). However, MaxiK channels do not appear to contribute to resting membrane potential, possibly because they have a very low open probability during the unstimulated state.…”
Section: Transporters In the Basolateral Membranementioning
confidence: 99%
“…Deletion of Kcnma1, which encodes MaxiK, impairs salivary K þ secretion, suggesting MaxiK to be the channel responsible for K þ efflux in salivary glands (Nakamoto et al 2008). A recent study showed that MaxiK channels are also expressed at the apical membrane of pancreatic duct cells in guinea pigs (Venglovecz et al 2011), which may contribute to the potentiation of secretin and CCK (or other Ca 2þ agonists such as cholinergic) response in pancreatic secretion (Gray et al 1990). However, the physiological role of the apical K þ channel in pancreatic duct cells is not fully understood at present, because unlike saliva, the major cation in pancreatic juice is Na þ and pancreatic duct cells do not secrete the bulk of K þ .…”
Section: Transporters In the Apical Membranementioning
confidence: 99%